2019
DOI: 10.6023/a19010040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of K-Doping on the Sodium-storage Performance of Sodium Vanadate Nanoplates

Abstract: Na-ion batteries with lower cost than Li-ion batteries would be developed to large-scale energy-storage device to store solar and wind energies. However, large radius renders Na + ions to insert into/extract out the layered transition metal oxides (LTMOs) sluggishly. To improve the intercalation dynamics of Na + ions, the interlayer spacing of crystals has to be expanded for those LTMOs that are capable of fast lithiation and delithiation. Herein, a LTMO based on vanadium is firstly doped with larger K + ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Vanadium-based compounds possess multivalent states of vanadium (from V 2+ to V 5+ ) and a wide interplanar spacing, which provides more possibilities to further extend their specific capacities by enabling the reversible Na + intercalation/deintercalation. [1][2][3][4][5][6][7][8] Among them, in numerous reports, sodium vanadium oxides have displayed satisfying capacities acting as cathode of SIBs when operated in a wider voltage window (1.5-4.0 V). [9][10][11][12][13][14][15][16] In our previous work, the sodium vanadium bronze (NaV 6 O 15 ) nanotubes of clew-like carbon-coated were designed, which could supply an exceptional capacity of 209 mAh g −1 at 25 mA g −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium-based compounds possess multivalent states of vanadium (from V 2+ to V 5+ ) and a wide interplanar spacing, which provides more possibilities to further extend their specific capacities by enabling the reversible Na + intercalation/deintercalation. [1][2][3][4][5][6][7][8] Among them, in numerous reports, sodium vanadium oxides have displayed satisfying capacities acting as cathode of SIBs when operated in a wider voltage window (1.5-4.0 V). [9][10][11][12][13][14][15][16] In our previous work, the sodium vanadium bronze (NaV 6 O 15 ) nanotubes of clew-like carbon-coated were designed, which could supply an exceptional capacity of 209 mAh g −1 at 25 mA g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Furthermore, a K + ‐doped sodium vanadate (Na 5‐x K x V 12 O 32 ) cathode was synthesized with a reversible capacity of 169 mAh g −1 at 26 mA g −1 . [ 8 ] Dong et al also synthesized hierarchicalzigzag Na 1.25 V 3 O 8 nanowires that showed the capacity of 172.5 mA h g −1 at 100 mA g −1 . [ 9 ] Indeed, the Na 1.1 V 3 O 7.9 nanobelts assembled by Yuan et al showed the capacity of 173 mA h g −1 at 25 mA g −1 .…”
Section: Introductionmentioning
confidence: 99%